Les cultures de l’étude à l’université dans leurs rapports avec les formes d’enseignement et la réussite académique - Coralie Touati (Éducation et Socialisation)
In this paper, the author examines studying at university as a social and didactical fact by bringing its structural patterns to light in two epistemologically contrasted subjects: law and education. Using a mixed methodology, articulating ethnographical observations, qualitative interviews and analytical statistics, the purpose is to explore the relations between studying, teaching and academic success. By dividing up these macro-variables into micro-variables, we demonstrate that academic success is more related to the quality than the quantity of studying interconnected with how students perceive their teachers’ expectations which certainly depends on students’ studying cultures and disciplines.